Facile Fabrication of CuO Nanoparticles Embedded in N-Doped Carbon Nanostructure for Electrochemical Sensing of Dopamine. (14th October 2022) - Sobahi, Nebras; Imran, Mohd; Khan, Mohammad Ehtisham; Mohammad, Akbar; Alam, Md. Mottahir; Yoon, Taeho; M. Mehedi, Ibrahim; Hussain, Mohammad A.; Abdulaal, Mohammed J.; A. Jiman, Ahmad
Abstract : In the present study, a highly selective and sensitive electrochemical sensing platform for the detection of dopamine was developed with CuO nanoparticles embedded in N-doped carbon nanostructure (CuO@NDC). The successfully fabricated nanostructures were characterized by standard instrumentation techniques. The fabricated CuO@NDC nanostructures were used for the development of dopamine electrochemical sensor. The reaction mechanism of a dopamine on the electrode surface is a three-electron three-proton process. The proposed sensor's performance was shown to be superior to several recently reported investigations. Under optimized conditions, the linear equation for detecting dopamine by differential pulse voltammetry is I pa ( μ A) = 0.07701 c ( μ M) − 0.1232 ( R 2 = 0.996), and the linear range is 5-75 μ M. The limit of detection (LOD) and sensitivity were calculated as 0.868 μ M and 421.1 μ A/ μ M, respectively. The sensor has simple preparation, low cost, high sensitivity, good stability, and good reproducibility.